A atividade de trabalho de professoras de escolas públicas: Ser professor é rebolar - Almeida, Monica Rafaela de (2010)
Studies regarding the teaching work in Brazil point out to a frame of precarious work conditions, low wages, full-time journey, social discredit and devaluation. Thus, the present study had as general objective to analyze the work activity of elementary public teaching female teachers from João Pessoa PB, in the perspective of learning the possible subjective mobilization of these workers in a work adverse quotidian. Specifically, we seek to learn the elements of the conditions and forms of the teachers work organization; we identify the regulation strategies of this activity and analyze the competences which the teachers utilize to accomplish their activities. In a way to assist this analysis, we have fallen back mainly upon the theoretical-methodological contributions, guarding its differences, from the Activity Ergonomics and the Work Psychodynamics, operated under the ergological perspective. The operationalization of this study has been developed from the articulation between different techniques which have made possible to emerge the wealth of human relations and the industrial activity in the work situations. To achieve that, we have utilized activity systematic observations, the counterpart instruction technique and mainly the constitution of Research Amplified Communities (CAPs). The analysis of the materials produced has been accomplished following the speech dialogic perspective, from suggestions of the bakhtinian thought. Twenty-five teachers have participated of the research, one man and twenty-four women, all of them proceeding from three elementary public schools, between the ages 21 and 60 years old. From the analysis of the materials produced, we have realized that the main reasons for the insertion and the professional formation of these workers in the mastership are deeply marked by the social relations of gender and class. We have observed the naturalization of the teaching work as a female work , what seems to have implications in the way of performing such work. Regarding the public policies which have been implanted in schools, we have realized that the teachers see them in general in a negative, limited way, since they do not change effectively the reality in schools. The teachers have related that there is not a previous discussion about the implantation of government programs in schools, what many times, instead of favoring their work, has generated overload, what makes difficult the accomplishment of their activities. Concerning the work conditions, we have observed that they are inadequate to the development of the work. The teachers complain, for instance, that the classrooms have inadequate acoustic and ventilation. Besides, they feel paralyzed by the lack of material resources in the exercise of their autonomy. We have verified a discrepancy between prescribed work and real work. The teachers see themselves before a prescription unable to foresee the diversity of situations which they face in the quotidian of schools, thus developing diverse ways of activity regulation, dealing with and inventing different manners of articulating the work, in order to guaranteeing the accomplishment of their activity. We have also learned the ingenuity of sensible intelligence mobilized by the workers in the development of their activities. We have verified yet the living of the nonrecognition of the teachers work by the society and the schools directions, in spite of the signaling of the recognition from students and colleagues. We have come to realize, however, that despite the difficulties found in the work situations, the teachers, through the use of their sensitiveness and creativity, develop diverse ways of activity regulation, giving new forms to the work and creating different ways of articulating themselves to it.